Antioxidant Properties of Popular Turmeric (Curcuma longa) Varieties from Bangladesh - Tanvir, E. M.; Hossen, Md. Sakib; Hossain, Md. Fuad; Afroz, Rizwana; Siew, Hua Gan; Khalil, Md. Ibrahim; Karim, Nurul (Wiley, 2017)
We investigated the aqueous and ethanolic extracts of different forms (local names: mura and chora) of turmeric (Curcuma longa) from the Khulna and Chittagong divisions of Bangladesh for their antioxidant properties and polyphenol, flavonoid, tannin, and ascorbic acid contents. The antioxidant activity was determined using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radicalscavenging activity and ferric reducing antioxidant power (FRAP) values. The ethanolic extract of Chittagong’s mura contained the highest concentrations of polyphenols (16.07%), flavonoids (9.66%), and ascorbic acid (0.09mg/100 g) and chora resulted in high yields (17.39%). The ethanolic extract of Khulna’s mura showed a higher DPPH radical-scavenging activity with the lowest 50% inhibitory concentration (IC50) (1.08